Pengaruh Kompetensi Pedagogik, Kompetensi Profesional, dan Sikap Profesi Guru Tehadap Kinerja Penilaian Guru di Sekolah Dasar - Nursiah Sappaile (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The aim of this research is to examine the effect of pedagogical competence, professional competence and attitude of teaching profession towards performance assessment of primary school teachers. The population is the primary school teachers who teach advanced classes who hold bachelor degree, possess five year teaching experience and competence certification. The sampling technique is stratified random sampling and get the sampling is 63 primary schools with 71 respondents. The pedagogical and professional competence scores are obtained from the UKG. The attitudes of teaching profession and the performance assessment is measured by instrument which is filled by the teachers and teacher respectively who were respondents in the study. The results show that: (1) there is a direct positive effect of pedagogical competence on teachers’ assessment performance, professional competence, and attitude of teaching profession on the teachers’ assessment performance; (2) there is a direct positive effect of pedagogical competence and professional competence on of the attitude of teaching profession.